Evaluation of a novel risk assessment method for self-harm associated with Borderline Personality Disorder. (October 2017) - Rao, Sathya; Broadbear, Jillian H; Thompson, Katherine; Correia, Anna; Preston, Martin; Katz, Paul; Trett, Robert
Objectives: Borderline personality disorder (BPD) is associated with frequent self-harm and suicidal behaviours. This study compared physician-assessed self-harm risk and intervention choice according to a (i) standard risk assessment and (ii) BPD-specific risk assessment methods. Methods: Forty-five junior and senior mental health physicians were assigned to standard or BPD-specific risk training groups. The assessment utilized a BPD case vignette containing four scenarios describing high/low lethality self-harm and chronic/new patterns of self-harm behaviour. Participants chose from among four interventions, each corresponding to a risk category. Results: Standard and BPD-specific groups were alike in their assessment of self-harm risk. Divergence occurred on intervention choice for assessments of low lethality, chronic risk ( p <.01) and high lethality, chronic risk ( p <.005). Overall, psychiatrists were more likely than their junior colleagues to correctly assess risk and management options. Conclusions: Although standard and BPD-specific methods are well aligned for assessing self harm-associated risk, BPD-specific training raised awareness of BPD-appropriate interventions, particularly in the context of chronic patterns of self-harm behaviour. Wider dissemination of BPD-specific risk training may enhance the confidence of mental health clinicians in identifying the nature of self-harm risk as well as the most clinically appropriate interventions for clients with BPD.